Performance of the National Institute of Infectious Diseases disability scale in HTLV-1-associated myelopathy/tropical spastic paraparesis - Schmidt, Felipe R; Coutinho, Evandro Sf; Lima, Marco A; Silva, Marcus Tt; Leite, Ana Ccb; Fonseca, Igor O [UNESP]; Araujo, Abelardo Qc (Springer Nature, 2023)
HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP) is a chronic disabling disease. However, there is a lack of an adequate and specific health measurement instrument validated and with good performance to assess their degree of physical disability. This led us to carry out this study and to evaluate the performance of Fiocruz's National Institute of Infectious Diseases (IDS) disability scale, a specific instrument for HAM/TSP. Ninety-two HAM/TSP patients participated in the study. One researcher applied the IDS, IPEC scale, Disability Status Scale (DSS), Expanded DSS (EDSS), Osame scale, Beck Depression Inventory, and the WHOQOL-BREF questionnaire. In parallel, blindly, and separately, other researchers applied the IDS. An inter-rater reliability analysis of the IDS, correlation analysis with the other scales, and depression and quality of life questionnaires were performed. The applicability of the IDS was also evaluated. The IDS showed high reliability in all scores. The inter-rater reliability test for the total IDS score was 0.94 (0.82-0.98) on its four dimensions. The scale adequately indicated the different degrees of disability, presenting a distribution similar to normal. There was a high correlation with the other scales (Spearman coefficients > 0.80, p < 0.001). The scale had good acceptance among users and a short application time. IDS for HAM/TSP was reliable, consistent, easy, and fast to use. It can be used for both prospective evaluations and clinical trials. The present study supports the IDS as a valid instrument to measure disability in patients with HAM/TSP compared to previously used scales.
Keywords: Disability evaluation; Evaluation study; HTLV-1-associated myelopathy; Psychometrics